Evaluating the Quality of Sentence Structures, Citations and References in Journal Articles: A Case Study in The Faculty of Mathematics and Science and The Faculty of Engineering - Dea Analisti (Passage, 2016)
This qualitative descriptive study attempts to evaluate the sentence types, the sentence logic, and the appropriateness of citations and references in the journal articles written by lecturers from the Faculty of Mathematics and Science and the Faculty of Engineering. The sentence analysis is based on the frameworks proposed by Alwi, Dardjowidjojo, Lapoliwa, and Moeliono (2003) and Oshima and Hogue (2007). Meanwhile, the analysis of citations and references is based on APA style (6th edition). The results of the sentence analysis show that complex sentences are the most frequent sentence type found in the journal articles. Moreover, the quality of sentence logic in the journal articles is good since most of sentences are written correctly and well structured. Citations and references analysis regarding the characteristics of reference sources show several important results: 1) books are the most frequent reference sources used in the journal articles, 2) the most common language used in the journal articles is Indonesian language, and 3) the sources published in 6 – 10 years are the most frequent source used in the journal articles. Regarding the appropriateness of citations and references, citations and references are mostly written inappropriately. In addition, mistakes related to the use of mechanics are the most common citation mistake and mistakes related to title are the most common reference mistake found in the journal articles. Overall, it can be concluded that the journal articles are good regarding the sentence logic but they need more improvement regarding citations and referencesKeywords: Sentence Types, Sentence Logic, Appropriateness, Citations, References